2021
DOI: 10.1007/s00406-021-01346-9
|View full text |Cite
|
Sign up to set email alerts
|

Long-term consequences of COVID-19 on cognitive functioning up to 6 months after discharge: role of depression and impact on quality of life

Abstract: Neurologic and psychiatric symptoms have been reported in the months following the infection with COVID-19. A low-grade inflammation has been associated both with depression and cognitive symptoms, suggesting a link between these disorders. The aim of the study is to investigate cognitive functioning 6 months following hospital discharge for COVID-19, the impact of depression, and the consequences on quality of life. Ninety-two COVID-19 survivors evaluated at 1-month follow-up, 122 evaluated at 3 months and 98… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
65
3
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(102 citation statements)
references
References 46 publications
(52 reference statements)
6
65
3
4
Order By: Relevance
“…According to Bonizzato et al, there seems to be a need for an adequate assessment of cognitive, behavioral, and psychological variables in post-COVID-19 patients [ 183 ]. This is consistent with the findings by Gouraud et al, who found a robust link between cognitive complaints and psychological distress [ 184 ], and Poletti et al, who found that depression is the best predictor of cognitive performance and of its improvement [ 185 ]. Hence, further research is critical to further describe a more granular-level picture of the long-term psychiatric functioning post-COVID-19.…”
Section: Discussionsupporting
confidence: 92%
“…According to Bonizzato et al, there seems to be a need for an adequate assessment of cognitive, behavioral, and psychological variables in post-COVID-19 patients [ 183 ]. This is consistent with the findings by Gouraud et al, who found a robust link between cognitive complaints and psychological distress [ 184 ], and Poletti et al, who found that depression is the best predictor of cognitive performance and of its improvement [ 185 ]. Hence, further research is critical to further describe a more granular-level picture of the long-term psychiatric functioning post-COVID-19.…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with meta-analytic evidence suggesting patients’ cognitive impairments after COVID-19 persist over time ( Ceban et al, 2022 ). Our findings corroborate with 3 longitudinal studies that identified cognitive impairments both 6 ( Poletti et al, 2021 ) and 12 months ( Méndez et al, 2021 ; Ferrucci et al, 2022) after COVID-19 hospitalisation, with most pronounced impairments within verbal learning, memory and executive function ( Méndez et al, 2021 ). While Ferrucci and colleagues observed improvement in verbal memory, attention, and processing speed, cognitive functions were still affected after 1 year, with processing speed, visuospatial and verbal memory being most affected (Ferrucci et al, 2022).…”
Section: Discussionsupporting
confidence: 89%
“…Depressive symptoms were found in a previous study to be the main predictor of impaired cognitive performance 6 months after hospitalisation with COVID-19 ( Poletti et al, 2021 ). Our finding that cognitive impairments 3 months after hospitalisation were moderately associated with subsequent depressive symptomatology after 1 year provides preliminary evidence that the opposite may also be the case.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…The most common sequelae were neurological and psychiatric symptoms. In this issue, Poletti and colleagues report cognitive functioning 6 months following hospital discharge for COVID-19 [ 3 ]. Neuropsychological and psychiatric evaluations were evaluated for COVID-19 survivors, healthy control group, and patients with major depressive disorder (MDD).…”
mentioning
confidence: 99%